PERCEPTIONS OF PHYSICIANS ABOUT CLINICAL PHARMACIST’S ROLE IN AL QASSIM’S HOSPITALS IN SAUDI ARABIA - Nahid Osman Ahmed; Mahfoudh A. M. Abdulghani; Sarah Fahad Alrebdi; Mohammed Faez Baobaid (Malaysian Journal of Public Health Medicine, 2017)
The objective of this study is to explore physician’s perception toward clinical pharmacy services and role of clinical pharmacists in governmental hospitals at Al-Qassim region. An observational cross-sectional survey was conducted. Results: 150 males and 39 females participated giving 75.5% (189 of 250) response rate. Physicians perceptions were found to be high (equal or more than 90% of frequency) in some clinical pharmacy services such as patients’ education and counselling, monitoring of patients’ responses to drug therapy including toxicity/side effects and provision of drug information to healthcare professionals. The physicians showed low perception (less than 76%) in the taking of patients’ medication history on admission, by clinical pharmacists. Conclusion: Physicians’ perception toward clinical pharmacy services and the role of clinical pharmacists was not found to be completely favourable. The reason of this mixed responses and to the accommodating feelings of clinical pharmacy services in clinical setting appear to relate to the state of infrastructure and environments of hospitals. The infrastructure and environments of hospitals need to be updated for an improved accommodation clinical pharmacy services.